Development of mismatch amplification mutation assays for the differentiation of MS1 vaccine strain from wild-type Mycoplasma synoviae and MS-H vaccine strains. - Zsuzsa Kreizinger; Kinga Mária Sulyok; Dénes Grózner; Katinka Bekő; Ádám Dán; Zoltán Szabó; Miklós Gyuranecz (PLoS ONE, 2017)
Mycoplasma synoviae is an economically significant pathogen in the poultry industry, inducing respiratory disease and infectious synovitis in chickens and turkeys, and eggshell apex abnormality in chickens. Eradication, medication and vaccination are the options for controlling M. synoviae infection. Currently there are two commercial, live, attenuated vaccines available against M. synoviae: the temperature sensitive MS-H vaccine strain and the NAD independent MS1 vaccine strain. Differentiation of vaccine strains from field isolates is essential during vaccination and eradication programs. The present study provides melt-curve and agarose gel based mismatch amplification mutation assays (MAMA) to discriminate the MS1 vaccine strain from the MS-H vaccine strain and wild-type M. synoviae isolates. The assays are based on the A/C single nucleotide polymorphism at nt11 of a HIT family protein coding gene. The melt- and agarose-MAMAs reliably distinguish the MS1 vaccine strain genotype from the MS-H vaccine strain and wild-type M. synoviae isolate genotype from 102 template number/DNA sample. No cross-reactions with other avian Mycoplasma species were observed. The assays can be performed directly on clinical samples and they can be run simultaneously with the previously described MAMAs designed for the discrimination of the MS-H vaccine strain. The developed assays are applicable in laboratories with limited facilities and promote the rapid, simple and cost effective differentiation of the MS1 vaccine strain.